Kajian Sistematis Efek Empiris, Farmakologis dan Aplikasi Klinis Formula Herbal Sheng Mai San - Aryaprana Nando; Hari Iskandar Kang; Fenny Yunita; Maya Septriana; Lismin Dirwanto (An-Najat, 2023)
Background: Shengmai Powder or Sheng Mai San (SMS) is a classic traditional Chinese herbal formula for enhancing qi and nourishing yin, and nowadays it is widely used for the treatment of arrhythmia, myocarditis, coronary heart disease, chronic heart failure and other heart diseases. Methods: This article is a systematic review of published evidences about the empirical and pharmacological effects of SMS available from Sciencedirect, PubMed and CNKI data bases. Results: In the classical book of TCM, SMS is stated to have the effect of enhancing Qi and Yin. Nowadays it is widely used to treat arrhythmia, myocarditis, coronary heart disease, heart failure, and others. Many pharmacologic and clinical studies indicate its mechanism and effectiveness for the treatment of those various diseases. Conclusion: The empirical effects of SMS have largely been proven to possess anti-oxidant, anti-inflammatory, metabolic, anti-hypoxia, immune-potentiation, and other effects, and to be effective in treatment of angina pectoris, myocarditis, coronary heart disease, heart failure, arrhythmia, and others.